Cellular immunity in COVID-19 and other infections in Common variable immunodeficiency - Løken, Ragnhild Øye; Fevang, Børre (Frontiers in Immunology, 2023)
Covid-19 has shed light on the role of cellular immunity in the absence of humoral response in different patient groups. Common variable immunodeficiency (CVID) is characterized by impaired humoral immunity but also an underlying T-cell dysregulation. The impact of T-cell dysregulation on cellular immunity in CVID is not clear, and this review summarizes available literature on cellular immunity in CVID with a particular focus on Covid-19. Overall mortality of Covid-19 in CVID is difficult to assess but seems not significantly elevated, and risk factors for severe disease mirrors that of the general population, including lymphopenia. Most CVID patients have a significant T-cell response to Covid-19 disease with possible cross-reactivity to endemic coronaviruses. Several studies find a significant but impaired cellular response to basal Covid-19 mRNA vaccination that is independent of an antibody response. CVID patients with infection only have better cellular responses to vaccine in one study, but there is no clear association to T-cell dysregulation. Cellular response wane over time but responds to a third booster dose of vaccine. Opportunistic infections as a sign of impaired cellular immunity in CVID is rare but is related to the definition of the disease. CVID patients have a cellular response to influenza vaccine that in most studies is comparable to healthy controls, and annual vaccination against seasonal influenza should be recommended. More research is required to clarify the effect of vaccines in CVID with the most immediate issue being when to booster the Covid-19 vaccine.